2002
DOI: 10.1017/s0954579402004078
|View full text |Cite
|
Sign up to set email alerts
|

Intervention research, theoretical mechanisms, and causal processes related to externalizing behavior patterns

Abstract: Intervention research with children and adolescents has suffered from a dearth of relevant theoretical grounding and from the lack of a reciprocal “feedback” mechanism by which clinical trials can inform relevant theorizing and conceptualization. There are hopeful signs, however, of increasing confluence between clinical efforts and theoretical models. Indeed, the key issue I discuss is how intervention studies can yield information about developmental and clinical theory as well as mechanisms related to psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 8 publications
1
101
0
2
Order By: Relevance
“…2,14 We used a randomized trial in an attempt to provide an experimental test of these theories because there is growing recognition that this is a rigorous method of testing hypotheses, [26][27][28]46 as it is always possible that the prospective effects observed in longitudinal studies are due to some unmeasured third variable. However, controlled trials greatly reduce this possibility because random assignment dramatically increases the likelihood that third variables are uncorrelated with the experimental manipulation by equally distributing them across conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,14 We used a randomized trial in an attempt to provide an experimental test of these theories because there is growing recognition that this is a rigorous method of testing hypotheses, [26][27][28]46 as it is always possible that the prospective effects observed in longitudinal studies are due to some unmeasured third variable. However, controlled trials greatly reduce this possibility because random assignment dramatically increases the likelihood that third variables are uncorrelated with the experimental manipulation by equally distributing them across conditions.…”
Section: Resultsmentioning
confidence: 99%
“…25 Randomized trials afford a unique opportunity to attempt to experimentally confirm findings from prospective risk factor studies, and such trials provide powerful tests of theories, given their relative immunity to the effects of third variables. [26][27][28] Further, a randomized trial is one of the few experimental paradigms that could potentially result in long-term decreases in depressive symptoms, providing an advantage over laboratory experiments that manipulate acute mood. In terms of affect regulation, if individuals engage in bulimic behaviors and substance use to reduce negative affect, it follows that an intervention that reduces depressive symptoms should produce consequent decreases in bulimic symptoms and substance use.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, early maladaptive parent-child interactions in relation to the development of externalizing problems (oppositional, overactive, and aggressive behavior) have taken center stage in preventive intervention research (Burke et al 2002;Hinshaw 2002). Several studies have suggested that the success of a parenting intervention is partly dependent on the parenting context in which the intervention is executed (e.g., Smith et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Het interventieonderzoek wordt te weinig gevoed door theoretisch noties en evenmin gebruikt om modellen van psychopathologie waarvan behandelingen zijn afgeleid, te toetsen. 7 In het algemeen weten wij wel wat werkt, maar we weten niet waarom. De kennis van werkzame mechanismen is echter van cruciaal theoretisch én praktisch belang.…”
Section: Mijnheer De Rector Magnificus Geachte Aanwezigenunclassified
“…Systematische ervaring die bijvoorbeeld is opgedaan in een gedragstherapie, kan kinderen die een hoge genetische kwetsbaarheid hebben voor problemen op het gebied van zelfregulatie hierin positief beïnvloe-den. 17 Ook al worden kinderen door uiteenlopende omgevingen beïnvloed, zoals leeftijdgenoten, 18 school, televisie, computers 19 en internet, toch gelden ouders van oudsher als de belangrijkste omgeving voor hun kind: 'As the twig is bent, so grows the tree', zo zegt het spreekwoord. Dit wordt geïllustreerd door de uitgebreide onderzoeksliteratuur naar 'ouder-op-kind'-effecten en het grote belang dat wordt gehecht aan gezinsrisicofactoren en sociale determinanten van opvoedersgedrag.…”
Section: Mijnheer De Rector Magnificus Geachte Aanwezigenunclassified